Composition, structure and properties of PZT-BT ceramics prepared by two-stage sintering - Vittayakorn W.C. (2014)
Ceramic solid solutions within the system (1-x)PZT-xBT, where x = 0.1, 0.2, 0.3, 0.4 and 0.5, were prepared by conventional mixed-oxide method combined with a two-stage sintering procedure. A sintering time of 2 h at 1000 °C followed by a second step in the temperature range of 1000-1200 °C for 2 h was employed to all samples and compared to the one-step sintering process. Phase formation, densification and microstructure of all ceramics were examined via X-ray diffraction (XRD), Archimedes method and scanning electron microscope (SEM). The results lead to the conclusion that the pure perovskite phase and high densification of (1-x)PZT-xBT ceramics with fine grain can be successfully achieved under suitable two-stage sintering conditions. © (2010) Trans Tech Publications.